Multiobjective optimization of efficiency, head, free passage and vibrations of two blade impeller for sewage pump with stationary front shroud - Sitniewski, Mikołaj; Skrzypacz, Janusz; Szulc, Przemysław; Janczak, Marcin; Lorenz, Witold (Instal, 2025)
This paper presents a multiobjective optimization procedure for a two-blade impeller in a sewage pump with a stationary front shroud. The optimization variables were the wrap angles on the front and back shroud, while the meridional cross-section and volute remained constant. The objective was to maximize efficiency, head, and free passage (e.g., minimizing blockage) while minimizing vibrations by reducing radial forces. A full factorial design with five levels was used for CFD (computational fluid dynamics) calculations. After selecting the optimal design, the results of initial and optimized impeller were validated experimentally. Numerical and experimental results demonstrated good agreement. The optimized impeller showed improvements: head increased by 38,4%, efficiency by 9,5%, and free passage by 8,3%. While CFD calculations predicted a reduction in averaged radial forces, vibration measurements on volute indicated an increase for the optimized impeller by 46,1%. This discrepancy suggests that radial forces may not be the primary factor influencing vibrations in this specific pump configuration. The findings of this study contribute to the development of more efficient and reliable sewage pumps.
Keywords: sewage pump; optimization; radial forces; vibrations; two blade impeller